Recovery and Molecular Detection of Lactobacillus plantarum Dad-13 from The Feces of Healthy Indonesian Volunteers After Intake of Fermented Milk - Hastuti, Sri; Rahayu, Endang Sutriswati; Mariyatun, Mariyatun; Nurfiani, Sri; Widada, Jaka (Indonesian Association of Food Technologists, 2025)
Lactobacillus plantarum Dad-13 is a promising probiotic candidate that can be developed as a starter culture in the production of fermented milk and is commonly isolated from dadih. However, for the bacteria to be considered a probiotic strain, they must survive and thrive in the human digestive tract. This study focused on investigating the recovery level of L. plantarum Dad-13 from fecal samples from healthy volunteers following the consumption of fermented milk. Healthy Indonesian adults (n = 30) were instructed to consume fermented milk containing L. plantarum Dad-13 for 20 days. For a duration of 20 days, 30 healthy Indonesian adults were instructed to consume fermented milk containing L. plantarum Dad-13. Fecal samples were collected at four distinct time intervals: 10 days before ingestion (F1); on day 10 and day 20 while consuming (F2 and F3, respectively); and 10 days after consumption (F4). The viable count of L. plantarum was evaluated by dilution and plating on Lactobacillus plantarum Selective Medium (LPSM). The molecular typing approach utilized repetitive sequence polymerase chain reaction (REP PCR) with the primer BOX A1R. The results indicated that consuming fermented milk led to an increase in the number of lactobacilli and lactic acid bacteria. A total of fifteen (15) isolates of lactic acid bacteria were selected from F1, F2, and F4 periods. The samples obtained from the stool of healthy adults during consumption showed over 99% similarity to L. plantarum Dad-13. Thus, the results showed that L. plantarum Dad-13, as a probiotic candidate, survives in the gut and can be recovered in fecal material.